Pigmented sorghum polyphenols as potential inhibitors of starch digestibility: An in vitro study combining starch digestion and untargeted metabolomics. (15th May 2020) - Rocchetti, Gabriele; Giuberti, Gianluca; Busconi, Matteo; Marocco, Adriano; Trevisan, Marco; Lucini, Luigi
Highlights: Pigmented sorghum (PS) flours were abundant in flavonoids and phenolic acids. Cooked PS flours had greater resistant starch (RS) content than white sorghum (WS) flour. Polyphenols modulated the in vitro starch digestibility after cooking. Anthocyanins and procyanidins discriminated PS vs WS flours during in vitro digestion. Kafirins, flavonoids, RS and hydrolysis index values were strongly correlated. Abstract: Polyphenols from five pigmented sorghum (PS) flours were in vitro evaluated as possible modulators of starch digestibility. White sorghum (WS) flour was used as control. Untargeted metabolomics depicted the phenolic composition of raw and cooked flours (obtained through heating at 100 °C for 30 min in water) highlighting differences in flavonoids and phenolic acids. Raw PS flours were characterized by greater tannin and kafirin contents when compared to WS, and, after cooking, PS flours had greater resistant starch (from 4.2 to 21.4 g /100 g dry matter), and lower starch hydrolysis index (HI) with respect to cooked WS. Multivariate statistics showed that flavonoids characterizing PS were the most discriminant compounds during the in vitro digestion. In addition, kafirin and total tannins content (on raw ingredients) along with the anthocyanin profiles (on cooked samples) were negative correlated with HI. Therefore, PS flours might be good candidates for the formulation of functional foods.